EFFECT OF BETA ADRENERGIC ANTAGONIST ON THE PRODUCTION OF TESTOSTERONE BY RAT'S LEYDIG CELLS - Khan, Umar Ali; Aslam, Muhammad; Saeed, S Abdul (Journal of Ayub Medical College Abbottabad, 2004)
Background: The Leydig cell is the source of the male sex steroids, or androgens, which are essential for the maintenance of the male phenotype, the male gonads, and spermatogenesis. It has been reported that patients taking beta-blockers experience sexual dysfunction. The purpose of this study was to explore the direct mechanism by which beta adrenergic antagonist exert its' effect on testosterone production by rat Leydig cells. Methods: Enzymatic dispersion of rat Leydig cell was done. About 85000 cells per tube were taken. After removal of endogenous testosterone by pre-incubation, The rat Leydig cells were incubated with varying concentrations of Atenolol: [Selective Beta-Adrenergic Antagonist} (10-6, 10-7 and 10-9 M) with or with out LH 250 IU for three hours to measure the testosterone release by RIA. Results: Atenolol, in varying concentrations caused a significant (P<0.05) reduction in testosterone release by the rat Leydig cells as compared to the basal release of testosterone in a dose-dependent fashion. Atenolol decreased the testosterone release by LH stimulated Leydig cells more significantly (P<0.001) as compared to the effects of Atenolol produced on non-stimulated Leydig cells. Conclusion: The current data indirectly suggest that Atenolol inhibits testosterone releasee via mechanism involving decrease production of cAMP but not affecting the enzyme activities of steroidogenesis. Key Words: Beta adrenergic antagonist; Atenolol; Leydig Cells; Testosterone